Pola Perkembangan Penyakit Bercak Bakteri (Xanthomonas campestris pv. vesicatoria) dan Penetapan Prediktor Waktu untuk Menduga Kehilangan Hasil Tomat - Budi Santosa; Muhammad Amri; Yurma Metri (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2024)
The aim of the research was to obtain the most precise pattern of development of bacterial disease (Xanthomonas campestris pv. vesicatoria) and determine the relationship between the intensity of bacterial spot disease and yield loss of tomato plants (Lycopersicum esculentum Mill.). The research was carried out in Solok Regency at an altitude of 388 m above sea level from June to December 2022. To determine the most appropriate pattern of disease development, two mathematical models were tested: Logistic and Gompertz’s models, which were corrected by Campbell and Madden as well as Neher and Campbell. The yield loss estimation method uses a single disease forecasting system with a single critical time type. The disease was measured at several plant ages according to the growth phase from the base point of 0 DAP, then at ages 26, 31, 36, 41, 46, 51, 56, 61, 66, and 71 days after planting. Variation in disease severity was created by inoculating plants through several inoculum densities. The results showed that the development of Xcv disease follows Gompertz’s model, and the critical time to determine the relationship between disease intensity and yield loss follows the rank regression model with a critical time at plant age of 31 days after planting.